2002
DOI: 10.1515/jpem.2002.15.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism with Prader-Willi Syndrome: Patient Report

Abstract: We report a 1 year-old female patient with severe hypotonia who has congenital hypothyroidism and Prader-Willi syndrome (PWS). At birth she was found to have congenital hypothyroidism caused by an ectopic sublingual thyroid gland and was commenced on thyroid replacement therapy. She continued to have severe motor delay and therefore further diagnostic evaluation was performed. PWS was confirmed by DNA and fluorescence in situ hybridization (FISH) analysis. This report emphasizes the need to further investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…Studies concerning thyroid hormone levels in PWS children are very limited. Congenital hypothyroidism has been reported in one girl with PWS 5 …”
Section: Introductionmentioning
confidence: 93%
“…Studies concerning thyroid hormone levels in PWS children are very limited. Congenital hypothyroidism has been reported in one girl with PWS 5 …”
Section: Introductionmentioning
confidence: 93%
“…Maternal uniparental disomy 14 (matUPD(14); Temple syndrome) is an infrequently described entity, first reported in 1991, 1 characterized by prenatal and postnatal growth retardation, hypotonia, feeding difficulties, small hands and feet, unusual face, truncal obesity, advanced bone age, early puberty and, in some, mild-to-moderate intellectual disability. 2,3 The majority (70-80%) of individuals with matUPD (14) inherit two maternal chromosomes 14. In the remaining individuals, the phenotype is caused by a normal (biparental) disomy but loss of function of the paternal allel due to a methylation disturbance. 2 The phenotype of matUPD (14) and, especially, the short stature and truncal obesity are similar to the phenotype in Prader-Willi syndrome (PWS) ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The majority (70-80%) of individuals with matUPD (14) inherit two maternal chromosomes 14. In the remaining individuals, the phenotype is caused by a normal (biparental) disomy but loss of function of the paternal allel due to a methylation disturbance. 2 The phenotype of matUPD (14) and, especially, the short stature and truncal obesity are similar to the phenotype in Prader-Willi syndrome (PWS) ( Table 1). 4 Growth hormone (GH) treatment in children with PWS has been shown to improve growth, body composition and muscle strength 2,5 and possibly has a positive effect on cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Sex steroids therapy not only induces pubertal changes but also improves bone mineral density (BMD) (Eiholzer, Grieser et al 2007, Cassidy andDriscoll 2009). Central hypothyroidism is seen in 19% of patients with PWS (Sher, Bistritzer et al 2002, Miller, Goldstone et al 2008) and treatment with thyroxine is important for the neuronal, metabolic and bone health. One study reported very high prevalence of central hypoadrenalism in children with PWS using over-night Metyrapone test (de Lind van Wijngaarden, Otten et al 2008).…”
Section: List Of Figures and Tablesmentioning
confidence: 99%
“…Hypothalamus secretes releasing hormones which controls the production of pituitary hormones and deficiencies of such releasing hormones is believed to result in common endocrinological abnormalities of PWS. For example growth hormone secretions defect (Grugni, Marzullo et al 2006), , central hypothyroidism (Sher, Bistritzer et al 2002) are due to the deficiency of growth hormone releasing hormone, and thyrotrophic releasing hormone respectively. Previously hypogonadism was thought to be due to hypogonadotrophic hypogonadism (Stephenson 1980) but recent reports suggest the primary gonadal failure is the major component of hypogonadism (Hirsch, Eldar-Geva et al 2009, Eldar-Geva, Hirsch et al 2010 latency, sleep onset REM periods and cataplexy independent of obesity (Vela-Bueno, Kales et al 1984, Kaplan, Fredrickson et al 1991, Manni, Politini et al 2001.…”
Section: 2: Pws and Hypothalamic Dysfunctionmentioning
confidence: 99%